Capability Conversion Gap in Accounting Systems and Digital Finance: Evidence from Semi-Urban MSMEs - Saraswati, Esti; Abdisamad Abdirahman Omar; Kristianto, Giovanny Bangun (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: Grounded in the Resource-Based View, this study examines the relationships between accounting information systems, financial inclusion, financial literacy, fintech adoption, and MSME performance in a semi-urban Indonesian context. It introduces the capability conversion gap to explain why accounting and digital financial resources do not automatically generate performance improvements. Research Methodology: A quantitative explanatory survey was conducted with 150 MSME owners and managers in South Purwokerto, Banyumas Regency, Central Java, Indonesia. Data were analyzed using descriptive statistics, instrument validity and reliability tests, Harman’s single-factor test, classical assumption tests, and multiple linear regression in SPSS 25. Results: Financial inclusion and fintech adoption are positively associated with MSME performance, whereas accounting information systems and financial literacy show statistically significant negative coefficients in the multivariate model. Fintech adoption had the largest positive standardized coefficient. Conclusions: Transaction-oriented digital financial resources are more readily converted into operational benefits, whereas accounting systems and financial knowledge require stronger behavioral implementation, bookkeeping discipline, and managerial routines. Limitations: The study uses cross-sectional, self-reported data from a sample dominated by microenterprises; therefore, the findings are interpreted as statistical associations rather than causal effects. Contributions: This study extends the MSME accounting and digital finance literature by explaining the asymmetric relationships between resources and performance from the perspective of the capability conversion gap. By distinguishing resource availability, capability development, and capability conversion, this study offers a context-specific explanation for why theoretically beneficial resources may not produce immediate performance gains.